Does Terrorism Still Spread Fear to ASEAN’s Financial Market? - Johan, Suwinto (JAS (Journal of ASEAN Studies), 2024)
The research aimed to examine the financial markets’ responses to terrorist attacks in Southeast Asia. Market reactions were a reflection of public sentiment. The market reaction was calculated using the stock index indicator and the currency exchange rate of the country relative to the US Dollar. The research employed a paired test to compare the period prior to and following the terrorist attack. The research used Wilcoxon Test to examine 38 terrorist attacks across four Southeast Asian nations: Indonesia, Thailand, Philippines, and Malaysia. The research concludes that the stock index exhibits both normal and abnormal returns between pre-incident and post-incident periods. Post-incident returns are higher than pre-incident returns. Stockholders are not required to sell their existing holdings in response to a terrorist attack. Between pre-incident and post-incident investors who do not invest in the capital or money markets, the foreign exchange market does not exhibit significant changes. Investors can profit by purchasing stock or foreign currency on the day of the incident or one day afterwards and selling it three days later.